Upaya meningkatkan motivasi dan prestasi Belajar matematika pada operasi bangun ruang melalui Pembelajaran kooperatif tipe STAD (student teams achievement division) - Rahayu Retnaningsih (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2017)
This study aims to (1) Know the increased motivation fourth grade students in elementary N Jombor Lor in learning through cooperative learning STAD. (2) to increase student achievement at the fourth grade of elementary school N Jombor Lor through STAD cooperative learning.This research is a class act. A resource in this study are principals, teachers, and students. Methods of data collection using tests, interviews, observations, and questionnaires. The results showed: (1) Application of STAD cooperative learning can boost the motivation of learners in the learning of Mathematics in Elementary School fourth grade students Jombor Mlati Lor sub-district. This can be seen from the percentage of students’ motivation is increased. Before being given the action of using STAD cooperative learning motivation of learners only reach the percentage of 32% or as much as 8 students. After a given action motivation of learners increased to 48% or as many as 12 students in the first cycle and to 80% or 20 students in the second cycle. (2) Application of STAD cooperative learning can improve learning achievement of learners in the learning of Mathematics in Elementary School fourth grade students Jombor Mlati Lor sub-district. Improved student achievement can be seen from the increase in the average and also the percentage of students learning completeness. Before the given action in the form STAD cooperative learning students’ average only able to reach a value of 66.20 with a percentage of 44% completeness. Having given the average value of the actions of learners has increased to 72 with a percentage of 60% in the first cycle and increased to 85 with a percentage of 92% in the second cycle